The Italian version of rheumatoid arthritis pain scale (IT-RAPS): psychometric properties on community and clinical samples - M. Tofani; M. Nobilia; G. Culicchia; G. Esposito; A. Savona; I. Tashi; A. Ventura; G. Galeoto (PAGEPress Publications, 2019)
This paper describes the validation process of the Italian version of the Rheumatoid Arthritis Pain Scale (ITRAPS), describing its translation and adaptation to Italian culture. The cultural adaptation and validation were based on data from a sample of people affected by rheumatoid arthritis (RA). The process required a forward and backward translation of the original language, reviewed by an expert panel. The adapted version of the RAPS was then tested on a community and clinical sample, in order to test its psychometric properties. The IT-RAPS was submitted to 122 people affected by RA. The data was analyzed using Cronbach's coefficient alpha and the Pearson product-moment correlation coefficients. The IT-RAPS showed an internal consistency reliability coefficient of 0.96. This is the first study reporting the validation and cross-cultural adaptation of the RAPS in Italian. The study's findings provided support for the IT-RAPS as a reliable and valid measurement of multidimensional pain in RA patients.